Increasing Activities And Science Learning Outcomes Factors Affecting Human Development And Growth with Picture and Picture Model in Class III Students of SDN Luwungragi 01 District Bulakamba Brebes Semester I 2018/2019 Academic Year - Sumarni, Nunung (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This research is  to be held, for knowing the enhancement of activity and result of student learning abaut the Factor wich influence of the growth and development of human by picture and picture method. The method of of  this research is contain of 3 siclus. The subject of this research is student from SDN Luwungragi grade III in year 2018/2019. There are 37 student. The technic  to accumulation the data of this research is fom notes data, formatif test, and obsevasion. The  data analysis  is used analiysis deskriptif  komparatif tecnick and analisis deskriptif kualitatif. The method of learning used picture and picture method. In the end of siclus III threre is changing in the student behaviour. The student who was pasif to be active. In the beginning the average of they are mark  is 62 to be 79 in the third siclus.whereas completeness learner of student there is in creased, in the beginning just 17 student who has completenesss but in the end to be 34 of student.It;s mean the sudent of SDN  Luwungragi 01 grade III has increased in activity and result of study of SAINS abaut the Factor wich influence of the growth and development by picture and picture method.